Features of the blood supply of a ventral part of the spine at different duration of the dynamic loadings - Сак [Sak A.], Андрій Евгенович (Slobozhanskyi Herald of Science and Sport, 2012)
A change blood supply of bodies of vertebrae and intervertebral disks in the conditions of the dynamic loads is studied. Work is executed on 90 white rats-males which hurried with the electronic meter of length at run during 20 and 90 days. It is shown, that protracted running in the in the decreasing of the level of blood supply of subchondral part of vertebrae bodies, boundary with disks. Changes are accompanied activating of processes of resorption of bone structures of vertebrae, growing in the disks of vessels and violation of their structural integrity. The moderate dynamic loadings, opposite, activated blood supply of vertebrae at the maintainance of structure of disks